Characterization of stress-strain relationships of elastoplastic materials: an improved method with conical and pyramidal indenters - Ma, Z.; Zhou, Y.; Long, S.; Zhong, X.; Lu, Chunsheng (Elsevier Ltd, 2012)
The load-displacement curve in indentation is widely used to extract elastoplastic properties of materials. It is believed that such a measurement is non-unique and a full stress-strain curve cannot be obtained with a sharp indenter or even plural and spherical indenters. By introducing a ratio of the additional residual area to the area of a profile indenter, we proposed a new set of dimensionless functions. Based on these functions and finite element simulations, analytical expressions were derived between indentation data and elastoplastic properties. It is shown that this method can effectively distinguish highly elastic and plastic solids (Cheng and Cheng, 1999) and mystical materials (Chen et al., 2007), which provides a useful guideline for properly using the indentation technique to measure elastoplastic properties of materials with conical and pyramidal indenters.